2013
DOI: 10.1073/pnas.1309629110
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor-dependent spatiotemporal dual roles of placental growth factor in modulation of angiogenesis and tumor growth

Abstract: Placental growth factor (PlGF) remodels tumor vasculatures toward a normalized phenotype, which affects tumor growth, invasion and drug responses. However, the coordinative and spatiotemporal relation between PlGF and VEGF in modulation of tumor angiogenesis and vascular remodeling is less understood. Here we report that PlGF positively and negatively modulate tumor growth, angiogenesis, and vascular remodeling through a VEGF-dependent mechanism. In two independent tumor models, we show that PlGF inhibited tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 40 publications
2
43
0
Order By: Relevance
“…To eliminate the host cell-derived VEGF-A from participating in VEGF-B-induced metastasis, we took a pharmacological approach to inhibit VEGF-A in mice bearing murine fibrosarcoma tumors. As expected, treatment of mice bearing vector-T241 tumors with an anti-mouse VEGF-A neutralizing antibody (VEGF-A blockade) (27)(28)(29) resulted in normalized vasculature (Fig. 5A).…”
Section: Anti-vegf-a Treatment Did Not Block Vegf-b-induced Cancer Mesupporting
confidence: 80%
“…To eliminate the host cell-derived VEGF-A from participating in VEGF-B-induced metastasis, we took a pharmacological approach to inhibit VEGF-A in mice bearing murine fibrosarcoma tumors. As expected, treatment of mice bearing vector-T241 tumors with an anti-mouse VEGF-A neutralizing antibody (VEGF-A blockade) (27)(28)(29) resulted in normalized vasculature (Fig. 5A).…”
Section: Anti-vegf-a Treatment Did Not Block Vegf-b-induced Cancer Mesupporting
confidence: 80%
“…At this time, We confirmed the formation of VEGF, PlGF homodimer, and VEGF/PlGF heterodimer through ELISA in transgenic mice placenta. 21 The result showed that there were no significant differences in the formation of heterodimer between WT and transgenic mice. Instead of it, PlGF homodimer formation was significantly induced because increased levels of PlGF homodimerization may cause placenta detachment ( Figure 5C).…”
Section: Regulation Of Angiogenic Signal In Placentamentioning
confidence: 94%
“…Exosomes derived from several types of cancer cells deliver EGFR to ECs and induce angiogenesis through VEGF/VEGFR2 signaling (120). Glioblastoma cells grown under hypoxic conditions were shown to produce exosomes that deliver pro-angiogenic factors such as IL8 and PDGF to ECs (121). An additional example is the transfer of tissue factor by tumor-cell derived exosomes to ECs, resulting in activation of GPCR proteaseactivated receptor 2 and subsequent upregulation of HB-EGF, promoting an angiogenic EC phenotype (122).…”
Section: Metastasis-related Interactions Between Cancer Cell-derived mentioning
confidence: 99%